Pandangan Al-Qur‟an Tentang Kurikulum - Hafizh, Muhammad; Salmiwati, Salmiwati (Institut Teknologi Pendidikan Indonesia, 2022)
The curriculum is a very decisive component of a system education, because the curriculum is a tool to achieve educational goals and at the same time a guide in the implementation of teaching at all types and levels of education. In Islam, the concept of the curriculum means manhaj, namely the bright path that is followed by educators and their students to develop their knowledge, skills, and attitudes. The Islamic education curriculum is Islamic education materials in the form of activities, knowledge, and experiences that are deliberately and systematically given to students to achieve the goals of Islamic education.